Kinematics of sprinting in children and youth - Vanderka, M.; Kampmiller, T. (New Studies in Athletics, 2013)
This study deals with ontogenetic characteristics of basic kinematic parameters of the running stride in terms of age and gender. Early identification of talent is important for the development of sprinters. Ideally, coaches should understand the parameters of running velocity that are relatively independent of age and demonstrate high individual development, or ontogenetic, stability and thus can be used as predictors of sprinting ability. A sample of more than 2,500 students aged 7 to 18 years sprinted at maximum velocity for 10m with a 15m flying start while kinematic indicators were collected and analysed. Running velocity and stride length were found to be highly dependent on age. However, there was a high ontogenetic stability of other key indicators (stride frequency, duration of support and flight phases), even if these parameters do deteriorate partially in the pre-pubescent period and at the beginning of the pubescent period. Based on their findings, the authors recommend that children and youths be evaluated on the basis of stride frequency and support phase duration. Those with results two or three standard deviations higher than the population averages should be considered as talented and directed to an appropriate programme of training and development.